Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
[tex]\begin{gathered} a)a_n=-36\cdot\frac{1}{3}^{n-1} \\ b)\text{ }a_n=\frac{1}{3}\cdot a_{n-1} \\ c)\text{ converges to -54} \\ d)\text{ s=-54} \end{gathered}[/tex]Step-by-step explanation:
The explicit and recursive formula for a geometric sequence is represented by the following:
[tex]\begin{gathered} \text{ Explicit formula:} \\ a_n=a_1\cdot r^{n-1} \\ \text{ Recursive formula:} \\ a_n=r\cdot a_{n-1} \\ \text{where,} \\ r=\text{ common ratio} \end{gathered}[/tex]The common ratio of the pattern is:
[tex]\begin{gathered} \frac{-12}{-36}=\frac{1}{3} \\ \frac{-4}{-12}=\frac{1}{3} \end{gathered}[/tex]Then, for the explicit formula:
[tex]a_n=-36\cdot\frac{1}{3}^{n-1}[/tex]Recursive formula:
[tex]a_n=\frac{1}{3}\cdot a_{n-1}[/tex]Now, to determine if the pattern converge or diverge:
[tex]\begin{gathered} \lvert r\rvert<1,\text{ the series converge to }\frac{a_1}{1-r} \\ \lvert r\rvert\ge1,\text{ the series diverges} \end{gathered}[/tex]Since the common ratio is less than 1, the series converges to:
[tex]\text{converges to }\frac{-36}{1-\frac{1}{3}}=-54[/tex]A sum of an infinite geometric series can be determined if it converges since this pattern converges, the sum would converge to;
[tex]\begin{gathered} S=\frac{a_1}{1-r} \\ S=\frac{-36}{1-\frac{1}{3}}=-54 \end{gathered}[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.